1990
DOI: 10.1530/acta.0.1230305
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of total and free thyroid hormones and thyroxinebinding globulin during normal puberty

Abstract: Thyroid hormones are essential for normal pubertal growth, yet the changes in total and, especially, free thyroid hormones and thyroxine-binding globulin during puberty have not been adequately defined. Serum from 39 normal children (20 girls, 19 boys) between the ages of 10 and 15 years were assayed for total T4, free T4, free T3 and thyroxine-binding globulin at 6-monthly intervals; the free hormone assays were valid, non-analogue methodologies. In the girls, free T4 levels fell from 15.7\m=+-\0.6 pmol/l at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 15 publications
(25 reference statements)
2
25
2
Order By: Relevance
“…In a more recent study with wild dolphins (Fair et al, 2011), thyroid hormone concentrations (i.e., total and free T 4 and total T 3 ) were not different between female and male dolphins after adjustment for age (juvenile and adult). Correspondingly, circulating concentrations of T 4 were not different between peripubertal girls and boys with matched ages at 10 and 15 y (Dunger et al, 1990). In the present study, thyroid hormone concentrations were not adjusted for age since actual ages were only known for juvenile females (mean, 2.9 y) and males (mean, 4.8 y) born under human care and not adults born in the wild.…”
Section: Discussionmentioning
confidence: 62%
“…In a more recent study with wild dolphins (Fair et al, 2011), thyroid hormone concentrations (i.e., total and free T 4 and total T 3 ) were not different between female and male dolphins after adjustment for age (juvenile and adult). Correspondingly, circulating concentrations of T 4 were not different between peripubertal girls and boys with matched ages at 10 and 15 y (Dunger et al, 1990). In the present study, thyroid hormone concentrations were not adjusted for age since actual ages were only known for juvenile females (mean, 2.9 y) and males (mean, 4.8 y) born under human care and not adults born in the wild.…”
Section: Discussionmentioning
confidence: 62%
“…Somerset (12) served as the control group. They were seen twice a year for measurements of height, weight and skinfolds.…”
Section: Subjectsmentioning
confidence: 99%
“…In a small longitudinal study (39 children, ranging in age from 10 to 15 years), there were significant fluctuations in both total and free T3 and T4 in association with pubertal stages of development (29). It has been suggested that these changes in thyroid hormone may play a role in the onset or evolution of puberty in children, and may serve as an effective adaptive mechanism for a period of rapid growth and increased energy requirements (28,29). One of the objectives of the current longitudinal study was to examine in greater detail the relationship between thyroid status and critical peripubertal events in a non-human primate model (male rhesus monkey).…”
Section: Introductionmentioning
confidence: 95%
“…In another crosssectional study in children in which data from boys and girls were combined, there was a transient increase in thyrotropin secretion and a resultant rise in T4 and tri-iodothyronine (T3) that preceded clinical pubertal changes (28). In a small longitudinal study (39 children, ranging in age from 10 to 15 years), there were significant fluctuations in both total and free T3 and T4 in association with pubertal stages of development (29). It has been suggested that these changes in thyroid hormone may play a role in the onset or evolution of puberty in children, and may serve as an effective adaptive mechanism for a period of rapid growth and increased energy requirements (28,29).…”
Section: Introductionmentioning
confidence: 99%